Penerapan Model Discovery Learning Berkolaborasi Google Classroom dan WhatsApp Group untuk Meningkatkan Kompetensi Siswa dalam Menulis Teks Eksplanasi - Waginah Dwi Nuryaningsih (Jurnal Paedagogy, 2021)
This study aims to describe the increase in activeness and learning outcomes of writing explanatory text in Indonesian subjects by implementing the Discovery Learning model through the online-based Whatsapp Group assisted by Google Classroom during the Covid-19 pandemic. The method used was classroom action research with a research design using the model of Kemmis and Mc Taggart which consisted of planning, implementing, observing, and reflecting stages. The subjects of this study were students of class VIII A SMP Negeri 3 Bojong, Pekalongan Regency. The technique of collecting data by means of interviews, observation, questionnaires and tests. While the data analysis technique used qualitative and quantitative descriptive analysis. The results of the research in the pre-cycle showed student activeness was 6.25%, in the first cycle it increased to 28.13%, and in the second cycle it increased by 15.62%. From the test results in the pre-cycle the average value was 69, in the first cycle it increased to 73, and in the second cycle it became 76. Students who achieved learning completeness in the pre-cycle 12,%, in the first cycle were 15.63, and in the second cycle it became 84.38%. It can be concluded that with the application of the Discovery Learning learning model through Google Classroom assisted by online-based Whatsapp Group during the Covid-19 pandemic, it can increase the activeness and learning outcomes of competency / explanatory text material for class VIII A students of SMP Negeri 3 Bojong.